MODERN ASPECTS OF SURGICAL TREATMENT AND DIAGNOSIS OF COLORECTAL CANCER (World Bulletin of Public Health, 2024)
Today, colorectal cancer remains the most common malignant neoplasm, the main method of which is surgical treatment. According to Global Cancer Statistics, in 2020, the mortality rate from colorectal cancer was 9.4%, and the number of new cases was about 2 million.